Apatinib Plus Camrelizumab With/Without Chemoembolization for Hepatocellular Carcinoma: A Real-World Experience of a Single Center - Ju, Shuguang; Zhou, Chen; Yang, Chongtu; Wang, Chaoyang; Liu, Jiacheng; Wang, Yingliang; Huang, Songjiang; Li, Tongqiang; Chen, Yang; Bai, Yaowei; Yao, Wei; Xiong, Bin (Frontiers in Oncology, 2022)
Objective This study was conducted in order to compare the efficacy and safety of transarterial chemoembolization (TACE) plus apatinib plus camrelizumab (TACE+AC) and apatinib plus camrelizumab (AC) in the treatment of unresectable hepatocellular carcinoma (HCC) in a real-world setting. Methods In this single-center retrospective study, the data of patients with unresectable HCC who had received TACE+AC or AC treatment during March 2017 to May 2021 were assessed. Patients in the AC group received intravenous administration of camrelizumab 200 mg every 3 weeks and oral apatinib 250 mg/day treatment. Patients in the TACE+AC group received the same dose of camrelizumab and apatinib 1 week after TACE. The primary endpoint of the study was overall survival (OS), objective response rate (ORR), disease control rate (DCR), and adverse events (AEs) as the secondary endpoints. Results A total of 108 patients were enrolled in the study. There were 52 patients in the AC group and 56 patients in TACE+AC group. Median OS was significantly longer in the TACE+AC group than in the AC group (24.8 vs. 13.1 months; P = 0.005). Patients in the TACE+AC group achieved a higher ORR [24 (42.9%) vs. 9 (17.3%), P = 0.004] than those in the AC group. Patients in the TACE+AC group also achieved a higher disease control rate (DCR) [48 (85.7%) vs. 30 (57.7%), P = 0.001] than patients in the AC group. There was no significant difference in the incidence of AEs related to apatinib and camrelizumab between the two groups, except for gastrointestinal reaction (P > 0.05, all; P < 0.05, gastrointestinal reaction). Conclusion TACE plus apatinib plus camrelizumab significantly improved OS, ORR, and DCR over apatinib plus camrelizumab in patients with unresectable HCC. AEs were tolerable and manageable.